The Innovative Method of Purifying Polluted Air in the Region of an Inversion Layer - Jędrzejek, F.; Gryboś, D.; Zyśk, J.; Leszczyński, J.; Szarłowicz, K.; Stobiński, M.; Kubica, B.; Suwała, W. (Frontiers in Environmental Science, 2021)
Formation of the inversion layer causes a lack of vertical movement of the atmosphere and the occurrence of long-lasting high concentrations of pollution. The new invention makes use of shock waves, created by explosions of a mixture of flammable gases and air. These shock waves destroy the structure of the temperature inversion layer in the atmosphere and restore natural convection. Restoring vertical movements within the atmosphere causes a reduction in air pollution at the ground level. The system was tested at full technical scale in the environment. Preliminary effects indicate an average 24% reduction in PM10 concentration in the smog layer at ground level up to 20 m, with the device operating in 11-min series consisting of 66 explosions. It was also shown that the device is able to affect a larger area, at least 4 km2.